The project of ontological phenomenology - Bęben, Dariusz (Folia Philosophica, 2003)
The article presents an outline of the philosophical opinions of Adolf Reinach (1883-1917). The branch of phenomenology, besides Husserl’s transcendental and Heidegger’s existential one, that has been recently the most systematically developed is the ontological phenomenology represented by Husserl’s Munich and Göttingen students. The most outstanding representative of ontological phenomenology was Adolf Reinach. His project of common ontology was clearly motivated by Husserl’s idealism and his conception of the state of affairs, i.e. the material state a priori, became the foundation of modern ontology.